Cycles in graphs - Alspach, B. R. (Brian Roger), 1938-; Godsil, C. D. (Christopher David), 1949- (North-Holland mathematics studies, 1985)
This volume deals with a variety of problems involving cycles in graphs and circuits in digraphs. Leading researchers in this area present here 3 survey papers and 42 papers containing new results. There is also a collection of unsolved problems.